Efektivitas Psikoedukasi Wawasan Kebangsaan untuk Menurunkan Kecenderungan Radikalisme pada Mahasiswa - Ariyanto, Eko April; Haque, Sayidah Aulia Ul; Syafii, Achmad Rizal (Philanthropy: Journal of Psychology, 2019)
This research is motivated by the growing understanding of radicalism in Indonesia, including among the young generation of Indonesia. The younger generation should be the hope of the nation to continue the struggle of the predecessors to advance Indonesia, but if the young generation has been exposed to radicalism, it is necessary to provide an intervention in this case in the form of psychoeducation. The purpose of this study was to determine the effect of "Nationality Insight" psychoeducation on the emergence of radicalism in students. This study uses a comparative quantitative approach with data collection using non-probability sampling techniques in the population at the University August 17, 1945. The results of the Paired Sample T Test obtained significance of 0.104> 0.05. The results of the Paired Sample T Test on the pre-test and post-test scales in the group treated in the form of Nationality Psychoeducation obtained a significance of 0,000